أثر الـمنطق والفقه في نشأة النحو العربي - عوض, سامي; عبد الرحيم, خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعتقد بعض الباحثين والدارسين أن للمنطق والفقه أثراً في النحو العربي, ومن خلال هذا البحث سأحاول أن أبيّن بُعد نحونا عن المنطق والفلسفة وخاصة اليونانية. فقد أرسى علماؤنا القدامى أسس هذا العلم قبل دخول المنطق والفلسفة إلى ديارنا العربية, حيث أسس المأمون بيت الحكمة سنة خمس عشرة ومئتين للهجرة, ومعظم علمائنا كالخليل بن أحمد وسيبويه, والكسائي, والفرّاء, قد توفوا قبل ذلك بسنوات, ولكن الفقه كان له أثر واضح في الدرس النحوي, خاصة في معالجة المسائل, وتقسيم الأفكار, وعناوين الكتب, والتعليل.., والفقه ابن البيئة العربية لذلك كان له هذا التأثير واضح في علماء اللغة والنحو, ومما ساعده على ذلك أن معظم علماء اللغة والنحو كانوا على علم ودراية بالفقه من حيث هو أحد فروع علم الدين, الذي هو محور دراستهم, فكلهم يهدف بدراسته إلى خدمة النص القرآني, فالدرس اللغوي العربي نشأ وتطور في مناخ عربي, ومن ثم فإن محاولة فهمه من خارج هذا المناخ تؤدي إلى أخطاء كثيرة . Some researchers and scholars believe that logic and jurisprudence have an impact on Arabic syntax. Through this research, I will try to show how our syntax is distancing itself from logic and philosophy, especially the Greek one. Our ancient scholars laid the foundations of this science right before the emergence of logic and philosophy in the Arab region, where Al-Mammon established The Wisdom House in 215 a.h. Most of our scholars like Al-Khalid ibn Ahmed. Subway, Alexei, and al-fara died some years ago before this establishment. But jurisprudence had a clear effect on the syntactic class, especially in processing questions, dividing ideas, titles, and explanation, etc. In addition, being Arab in nature, jurisprudence also had a clear effect on linguists and syntacticians. What was conducive in this respect was that most linguists and syntacticians were aware of and familiar with jurisprudence being one of the branches of theology represented by the Quran. Moreover, the Arabic linguistic class developed in an Arab milieu. So, attempting to make it understandable outside this ambiance leads to making many mistakes.